2004
DOI: 10.1159/000074322
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Sediment Podocalyxin in Children with Glomerular Diseases

Abstract: Background: In an immunofluorescence study using antibody to podocalyxin, we reported that urinary excretion of podocytes reflected podocyte injury in glomeruli. However, this method has some problems, since it is basically urine cytology. To overcome problems with this test, we measured whole podocalyxin content in urine sediment by enzyme-linked immunosorbent assay (ELISA). Methods: Urinary sediment podocalyxin (u-sed-PCX) content of the first morning urine was quantified by ELISA after solubilization by det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…Kanno et al measured levels of u-PCX in children with glomerular diseases such as IgAN and concluded that u-PCX was a useful biomarker for estimating the severity of active glomerular injury and urinary index of acute extracapillary abnormalities in children (21). Habara et al reported that levels of u-PCX in adults with various forms of active GN were significantly higher than those in patients with chronic GN in long-term remission (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kanno et al measured levels of u-PCX in children with glomerular diseases such as IgAN and concluded that u-PCX was a useful biomarker for estimating the severity of active glomerular injury and urinary index of acute extracapillary abnormalities in children (21). Habara et al reported that levels of u-PCX in adults with various forms of active GN were significantly higher than those in patients with chronic GN in long-term remission (10).…”
Section: Discussionmentioning
confidence: 99%
“…The epitopes on mAbs were characterized using PCX-Intra. The hybridomas were produced in immunized BALB/C mice as previously described by Tsutsumi et al (20), and then selected and subcloned according to the immunofluorescence pattern that was assayed on human renal cortex or ELISA using plates coated with wheat germ agglutinin-binding as reported elsewhere (21). Among the positive clones, mAb no.…”
Section: Production Of Mabs To Pcxmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few studies of potential biomarkers for crescentic GN. Kanno and colleagues 12 showed that levels of urinary sediment podocalyxin are elevated in children with cellular crescents. Levels of urinary macrophage migration inhibitory factor and matrix metalloproteinase activity are reportedly higher in patients with crescentic GN and ANCA-associated GN than in healthy controls, 13,14 but the levels are not significantly higher than in patients with other glomerular diseases.…”
mentioning
confidence: 99%
“…Increased urine sediment levels of nephrin and podocin have been detected in patients with diabetic nephropathy and active lupus nephritis (27,28). Similarly, increased levels of podocalyxin have been found in the urine sediment of patients with IgA nephropathy, lupus nephritis and post-streptococcal glomerulonephritis (29).…”
Section: Biomarkers Of Kidney Structural and Cellular Injurymentioning
confidence: 91%